¿Cómo mejorar la eficacia del ecommerce en tiendas por departamento en Perú? - Callirgos Paredes, Luciana (2021)
Within the framework of the technological evolution that the business world is going through today, the retail war has moved to a new field: virtual stores or ecommerce. Despite this new situation, there are still many companies that do not have synergy between the online sales channel and the physical store, since each area works independently. This means that the company cannot obtain the best results, since it is not generating omnichannel and, therefore, all the resources they have are not being exploited to the maximum. On the other hand, there is still a lot of mistrust on the part of customers, since various web platforms of different companies are quite complex and customers reject the idea of ¿¿starting to use them. Likewise, many companies do not know how to handle the communication of their commercial strategy to customers, such as the security of the transaction, the after-sales service, among others, causing that customers do not feel sufficient security and are not tempted to make the purchase online . It is in this context that this research is carried out, with the aim of finding out the possibilities of improving the efficiency of e-commerce in the Peruvian retail market, specifically in department stores.